The origin of non-porphyritic pyroxene chondrules in UOCs: Liquid solar nebula condensates? - Engler, Almut (2007)
A total of 56 non-porphyritic pyroxene and pyroxene/olivine micro-objects from different unequilibrated ordinary chondrites were selected for detailed studies to test the existing formation models. Our studies imply that the non-porphyritic objects represent quickly quenched liquids with each object reflecting a very complex and unique evolutionary history. Bulk major element analyses, obtained with EMPA and ASEM, as well as bulk lithophile trace element analyses, determined by LA-ICP-MS, resulted in unfractionated (solar-like) ratios of CaO/Al2O3, Yb/Ce as well as Sc/Yb in many of the studied objects and mostly unfractionated refractory lithophile trace element (RLTE) abundance patterns. These features support an origin by direct condensation from a gas of solar nebula composition. Full equilibrium condensation calculations show that it is theoretically possible that pyroxene-dominated non-porphyritic chondrules with flat REE patterns could have been formed as droplet liquid condensates directly from a nebular gas strongly depleted in olivine. Thus, it is possible to have enstatite as the stable liquidus phase in a 800 × Cl dust-enriched nebular gas at a ptot of 10-3 atm, if about 72% of the original Mg is removed (as forsterite?) from the system. Condensation of liquids from vapor (primary liquid condensation) could be considered as a possible formation process of the pyroxene-dominated non-porphyritic objects. This process can produce a large spectrum of chemical compositions, which always have unfractionated RLTE abundances. Late stage and subsolidus metasomatic events appear to have furthered the compositional diversity of chondrules and related objects by addition of moderately volatile and volatile elements to these objects by exchange reactions with the chondritic reservoir (e.g., V, Cr, Mn, FeO as well as K and Na). The strong fractionation displayed by the volatile lithophile elements could be indicative of a variable efficiency of metasomatic processes occurring during and/or after chondrule formation. Histories of individual objects differ in detail from each other and clearly indicate individual formation and subsequent processing. © 2007 Elsevier Inc. All rights reserved.